Remote sensing of Land Use and Land Cover changes in semi-arid regions: a Google Earth Engine approach for urban planning in Djebel Ouahch (Constantine, Algeria) - Benoumeldjadj, Maya; Bouarroudj, Nedjoua; Rached-Kanouni, Malika; Bouchareb, Abdelouahab (Bulletin of Geography. Physical Geography Series, 2025)
This study provides a critical analysis of land use and land cover changes in the Djebel Ouahch region (Constantine, Algeria) across three significant time periods: 1984, 2004 and 2023. Using remote sensing data and spectral indices, the research reveals important trends in urban development and vegetation cover. The Normalised Difference Built-up Index (NDBI) showed notable variations: from minimal urban development (0.01) in 1984, to a significant decrease (to –0.06) in 2004 following shantytown eradication programmes, and a slight increase (to –0.03) by 2023 due to rural housing initiatives launched in 2008. Concurrently, the Normalised Difference Vegetation Index (NDVI) demonstrated an overall positive trend, increasing from 0.45 in 1984 to 0.55 in 2023, despite a temporary decline in 2004. This research contributes significantly to understanding urban-environmental dynamics in semi-arid regions and provides valuable insights for policymakers and urban planners. The findings are particularly relevant for developing sustainable urban development strategies that balance population needs with ecosystem preservation in rapidly evolving regions.